OP0055-HPR Preferences for self-management and support services in patients with inflammatory arthritis: a danish nationwide cross-sectional study. (15th June 2017) - Hammer, NM; Flurey, C; Jensen, KV; Andersen, L; Esbensen, BA
Abstract : Background: During recent years the medical treatment of inflammatory arthritis (IA) has improved and become more efficient. However, many patients still continue to experience serious negative impact on both their physical and psychosocial health and wellbeing. Therefore, it is essential to identify patients' needs for support for managing IA in everyday life. Objectives: To explore preferences for self-management and support services in patients with inflammatory arthritis. Methods: Adult patients with IA (rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA)) were invited through The Danish Rheumatism Organization, arthritis networks, and hospitals' rheumatology departments across the country to participate in a cross-sectional study using online survey methodology. The questionnaire included questions on patient's interest in participation (requiring an answer of yes or no) in a total of 30 different self-management and support services within eight overall categories (i.e. discussion groups, one-to-one sessions, question and answer sessions, organised talks, physical activity, education sessions, raising arthritis awareness events, and online services), and preferences regarding practical issues of taking part. Descriptive statistics were applied. Results: In total, 664 patients (85% female) responded, of which 53% had RA, 27% had PsA and 20% had axSpA. Respondents' mean age was 50 years (SD=13), and median disease duration was 10 years (IQR=4–16). Of the 30 different self-management and support services, the most popular was Online service: Website for information (about symptoms, treatment and self-management of arthritis) with 91% of the respondents indicating interest. This was followed by One-to-one session with a rheumatologist (about coping with arthritis) (89%) and Organised talks by researchers (about current rheumatology research) (83%). Also, One-to-one session with a nurse, One-to-one session with a physiotherapist, and Education session on managing symptoms were all chosen by more than 80% of the respondents. The vast majority of respondents (81%) indicated to prefer a group with no fixed commitments and an advertised time table. Regarding timing of support, the majority (70%) indicated that self-management and support services should optimally be offered whenever needed. However, respondents also stated it would be helpful within the first six months of being diagnosed (49%) as well as during flares (30%). Conclusions: Patients with IA show high overall interest in taking part in self-management and support services. Especially, websites for finding disease related information, one-to-one sessions with health professionals, organised talks about rheumatology research and education on symptom management are requested. The preference regarding practical issues seems to be for a flexible delivery according to the patients' fluctuating needs during their illness course. Disclosure of Interest: None declared